Zero days - Ware, Ruth (Scout Press, 2023)
"Hired by companies to break into buildings and hack security systems, Jack and her husband, Gabe, are the best penetration specialists in the business. But after a routine assignment goes horribly wrong, Jack arrives home to find her husband dead. To add to her horror, the police are closing in on their suspect--her. Suddenly on the run and quickly running out of options, Jack must decide who she can trust as she circles closer to the real killer in this unputdownable and heart-pounding mystery from an author whose "propulsive prose keeps readers on the hook and refuses to let anyone off until all has been revealed" (Shelf Awareness)"--